Voltammetry at spatially heterogeneous electrodes - Davies, T; Banks, C; Compton, R (2005)
Recent advances are overviewed which enable simulation of the voltammetric behaviour of surfaces which respond in an electrochemically spatially heterogeneous fashion. By use of the concept of a "diffusion domain" computationally expensive three-dimensional simulations may be reduced to tractable two-dimensional equivalents. In this way the electrochemical response of partially blocked electrodes and microelectrode arrays may be predicted, and are found to be consistent with experimental data. It is, furthermore, possible to adapt the "blocked" electrode analysis to enable the voltammetric sizing of inert particles present on an electrode surface. Finally theory of this type predicts the voltammetric behaviour of electrochemically heterogeneous electrodes-for example composites whose different spatial zones display contrasting electrochemical behaviour toward the same redox couple. © Springer-Verlag 2005.